ASSOCIATION NOTES. - Austin, E. Burl (The Accounting Review, 1958)
The article presents appointments and transfers that took place in various universities and colleges of the U.S. Earl E. Pontius has been appointed assistant professor in accounting in the George Washington University, Washington, D.C. The University of Alabama, Alabama was host in April and May 1958 to the twenty sixth Semi-Annual Certified Public Accountants Review Courses offered during a five week period. In Los Angeles State College, California, George N. Francis has been promoted to full professor, Sol. S. Buchalter has been transferred to San Fernando State College in the rank of assistant professor, E. Kennedy Cobb, formerly of Haskins & Sells and Bradley University, will join the staff in the fall term as assistant professor, E.I. Fjeld, formerly of City College of New York (retired), is continuing on the staff for the fall term, 1958 and Willard D. Horwich has joined the staff as assistant professor. George W. Collins has been selected to attend the Joint Committee on Education, representing the American Securities Business, in New York City in June and July 1958. The meetings are to be held in the Graduate School of Business Administration at New York University.